KONTEKS HUBUNGAN HUKUM DAN PELINDUNGAN KONSUMEN DALAM PEMASARAN PRODUK ASURANSI MELALUI BANCASSURANCE - elisatris gultom (Jurnal Yuridis, 2024)
Bancassurance allows public access to insurance products. However, bancassurance raises several legal issues. The aim of this research is to determine the legal relationship between insurance companies and banks as well as the legal protection of insurance consumers. The method used is normative juridical, namely a review of laws and regulations that are relevant to legal issues, especially related to the implementation of bancassurance in Indonesia, while this research is analytical descriptive, namely obtaining a comprehensive picture regarding the implementation of bancassurance in Indonesia, for further analysis regarding aspects bancassurance legal relations and consumer legal protection. The research results conclude: The legal relationship between insurance companies and banks through bancassurance is cooperation in marketing insurance products, where the bank is only tasked with marketing insurance products without the authority to negotiate and pay claims for insurance products; Consumer protection is provided not only regarding the insurance products offered but also the credibility of the insurance companies that issue insurance products and banks that market insurance products. In order to guarantee the security and confidentiality of customer data, it is necessary to draw up confidentiality pacts by insurance companies and banks that state that customer personal data is not used outside its intended purpose to prevent misuse.